The Effectiveness of Lape Traditional Game Skills on Students’ Physical Fitness and Learning Outcomes During the Covid-19 Pandemic (Journal of Physical Education and Sports, 2022)
This study aims to determine the effectiveness of traditional lape game skills on students’ physical fitness and learning outcomes during the Covid-19 pandemic. This study uses a quasi-experimental method using a two-group pretest-posttest design. The sampling technique used was total sampling. The sample of this study was 22 students of class XI SMA Negeri 1 Woja. This data is then followed by testing the requirements of the paired T-test analysis at the significance level (0.05). Based on the results of data analysis and discussion, it was concluded: (1) There are traditional lape game skills on students' physical fitness during the covid-19 pandemic with a significance level of 0.000 <0.05 on the physical fitness variable getting an average pretest value of 15.68 while the posttest increased by 18.56. (2) There are traditional lape game skills on student learning outcomes during the covid-19 pandemic with a significance level of 0.043 <0.05 in the lape game variable with an average pretest value of 17.50 while the posttest value increased by 23.23. (3) There is a difference in traditional lape game skills on physical fitness and student learning outcomes during the Covid-19 pandemic with a significance value of 0.000 with a score of 20.36 for physical fitness training and a significance value of 0.043 with a score of 23.23 for a traditional lape game.